2018
DOI: 10.1038/s41419-018-0440-1
|View full text |Cite
|
Sign up to set email alerts
|

Fbxw11 promotes the proliferation of lymphocytic leukemia cells through the concomitant activation of NF-κB and β-catenin/TCF signaling pathways

Abstract: The ubiquitin–proteasome system (UPS) participates in both physiological and pathological processes through the posttranslational regulation of intracellular signal transduction pathways. F-box and WD-40 domain protein 11 (Fbxw11) is a component of the SCF (Skp1–Cul1–F-box) E3 ubiquitin ligase complex. Fbxw11 regulates various signal transduction pathways, and it may have pathological roles in tumorigenesis. However, the role of Fbxw11 in the development of leukemia and the underlying mechanisms remain largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…Consistently, β-TrCP2 depletion inhibits the proliferation of MEFs [33]. Conversely, β-TrCP2 overexpression accelerates lymphocytic leukemia cell proliferation in vitro and tumorigenesis in vivo [39]. Therefore, targeted inactivation of β-TrCP2 possessing oncogenic properties might be a promising anticancer therapy strategy.…”
Section: Discussionmentioning
confidence: 90%
“…Consistently, β-TrCP2 depletion inhibits the proliferation of MEFs [33]. Conversely, β-TrCP2 overexpression accelerates lymphocytic leukemia cell proliferation in vitro and tumorigenesis in vivo [39]. Therefore, targeted inactivation of β-TrCP2 possessing oncogenic properties might be a promising anticancer therapy strategy.…”
Section: Discussionmentioning
confidence: 90%
“…To date, no study has reported the effect of the interaction of CUL7 and Fbxw11 in cancer. Wang et al revealed that the Fbxw11 protein level was aberrantly upregulated in patients with lymphocytic leukemia, and the effects were mediated by the stimulation of cell-cycle progression and activation of the NF-κB and β-catenin/TCF signaling pathways rather than the induction of apoptosis 93 . Moreover, the Fbxw11 protein level is increased in mouse skin tumors and promotes cell growth 94 , migration, and invasion 95 through activation of the NF-κB signaling pathway.…”
Section: The Ring Box Protein Rbx1 Adaptor Skp1 and F-box Proteins mentioning
confidence: 99%
“…NF-κB and β-catenin/TCF play important roles in CC progression [23, 24]. Since FBXW11 could activate both the NF-κB and β-catenin/TCF signaling pathways [25], we suspected that lncRNA PCGEM1 may regulate these two signaling pathways through FBXW11. For confirmation, a dual luciferase reporter system was used and the results showed that both the NF-κB and β-catenin/TCF signaling pathways were enhanced by PCGEM1 overexpression, while knockdown of FBXW11 abolished this upregulation (Fig.…”
Section: Resultsmentioning
confidence: 99%